A Pilot Study to Evaluate HEMA based Desensitising Agent and 980 nm Diode Laser in Dentinal Hypersensitivity - Ahirwar, Anupama; Bhargava, Anuj; Meena, Sanjesh Kumar (Journal of clinical and diagnostic research, 2020)
Introduction: Dentinal Hypersensitivity (DH) presents as a short, intense pain emanating from exposed dentinal tubules. Many studies have concluded that mechanical, chemical or both factors increase the frequency of DH. Sealing of exposed dentinal tubule can be achieved with the use of Dental adhesives, restorations, Desensitising Agents (DA) and Lasers, each having their own mechanism of action. Aim: This clinical study was done to evaluate the efficacy of Hydroxy Methacrylate (HEMA) based DA and 980 nm diode laser in the treatment of DH. Materials and Methods: This two-arm parallel design split-mouth study was conducted on 30 adult patients attending the Dental Outpatient Clinic of Gandhi Medical College, Bhopal during the year December 2018 to January 2020 with clinically diagnosed high cervical DH (Charlie=3) occurring bilaterally in maxillary canine teeth. Scoring of baseline and postoperative DH was done utilising using Modified U.S. Public Health Service Criteria for DH Assessment. After recording the pretreatment baseline scores, mouth of each sample subject was divided bilaterally using split-mouth technique into Group A and Group B. The left side of patient’s mouth was designated as Group A in which a 10 W Diode Laser (980 nm) was used and right side of the patient’s mouth was classified as Group B, in which Shield Active (HEMA based) DA was used. The sensitivity score for both the groups was assessed immediately after application, after 24 hours, after seven days and after 21 days. Statistical Analysis was done by using Statistical Package for Social Sciences(SPSS) software version 22.0. Student’s t-test and repeated measures of ANOVA Test were applied. The p-value of less than 0.05 was considered statistically significant. Results: There was a statistically highly significant difference in sensitivity scores between both groups immediately after treatment p=0.038, after 24 hours, seven days and after 21 days. (p<0.001) depicting high efficacy of Diode lasers over DA. Repeated Measure of ANOVA was applied to find difference in mean score from baseline to 21 days. Immediately after application the results in Group A compared to baseline were statistically highly significant (p<0.001) and statistically significant in Group B (p<0.05). However, overall difference after 21 days compared to baseline were not significant in any group (p>0.05) depicting that the effect of both the desensitising therapies were not significant beyond 21 days in both the groups. Conclusion: Within the limits of this study, it can be concluded that both HEMA based DA and 980 nm diode laser were effective desensitisation treatment modalities for achieving immediate reduction of high cervical dentin hypersensitivity from baseline. Further, 980 nm Diode laser was found to be more efficacious and effective treatment option than HEMA based DA for treatment of DH.